P32 SELF–LEARN IMPLEMENTATION OF ULTRASOUND FOR THE STUDY AND ULTRASOUND–GUIDED PUNCTURE OF VASCULAR ACCESSES IN THE IMPLANTATION OF PACEMAKERS AND IMPLANTABLE DEFIBRILLATORS. (18th May 2022) - Lilli, A; Solarino, G; Della Tommasina, V; Del Meglio, J; Comella, A; Poddighe, R; Canale, M; Bertini, L; De Caro, F; Christou, A; Ferrali, E; Tognarelli, A; et al.
Abstract: Background: The vascular access represents a crucial phase in the management of complications related to the implantation of devices. After the use of the axillary vein, which allows the elimination of intrathoracic complications as well as the subclavian crush of the catheters, the ultrasound–guided approach could represent the next step for the reduction of vascular complications. Experience: All implants performed (n = 86) by an independent operator who implemented ultrasound to minimize complications related to central access were reviewed. During the first phase, the ultrasound–guided approach involved the study of vascular accesses before the start of the implant. The assessment took place before the preparation of the sterile field, for the localization of the axillary approach and for the study of the anatomical variants. It was immediately followed by the use of skin marks. The use of markers made it possible to attempt surgical isolation of the cephalic vein as a first approach. In case of failure, or the need for multiple accesses, the transition to central access could be facilitated by the presence of skin markers. This approach have not significantly modified the probability of successful axillary vein puncture without the use of venography (75% vs 71%, p NS). In the last phase all implants were performed with ultrasound–guided puncture with sterile technique before skin incision (n = 26). The procedures involved dual chamber (61%), single chamber (19%), CRTD (11%), dual chamber ICD. Ultrasound showed all cases of hypoplastic cephalic vein (15%). In the first three months of implementation, the success rate was 71.4% with 1 self–healing case of apical pneumothorax. In the following months the success rate rapidly increased to 94.1% (p < 0.05) with no pneumo or hemothorax. The median time to effective puncture was 28 seconds (8–450sec) in the second phase. It was possible to isolate the cephalic vein in 40% of cases for two or three chamber implants. Conclusions: The ultrasound study of the accesses performed before the incision allows to identify the anatomy and to define the course of the axillary vascular system and its relationships. When performed with a sterile approach, it allows direct ultrasound–guided puncture before the surgical incision, with a high success rate from the early stages of implementation.